1977
DOI: 10.1084/jem.145.6.1567
|View full text |Cite
|
Sign up to set email alerts
|

The identification in adult bone marrow of pluripotent and restricted stem cells of the myeloid and lymphoid systems

Abstract: The precise relationship between the stem cells for the lymphoid system and those for the blood-forming system is unclear. While it is generally assumed that the hemopoietic stem cell, the spleen colony-forming unit (CFU-S), is also the stem cell for the lymphoid system, there is little evidence for this hypothesis. To investigate the stem cells in these two systems, we irradiated bone marrow cells to induce unique chromosome aberrations in the stem cell population and injected them at limiting dilution into s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
148
0
8

Year Published

1981
1981
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 529 publications
(160 citation statements)
references
References 30 publications
4
148
0
8
Order By: Relevance
“…There would be prima facie evidence for such committed stem cells, able to yield only one or other type of lymphocyte, if procedures were found that differentially replenish the mature B and T compartments of repopulated irradiated hosts. Abramson et al (2) induced chromosome markers by irradiation and followed the progeny of uniquely marked individual stem cells. They found signs of a committed T stem cell in bone marrow.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There would be prima facie evidence for such committed stem cells, able to yield only one or other type of lymphocyte, if procedures were found that differentially replenish the mature B and T compartments of repopulated irradiated hosts. Abramson et al (2) induced chromosome markers by irradiation and followed the progeny of uniquely marked individual stem cells. They found signs of a committed T stem cell in bone marrow.…”
mentioning
confidence: 99%
“…T and B lymphocytes are descended from a common ancestor, a muhipotent stem cell (1,2). The question arises as to the stage at which these two lineages diverge.…”
mentioning
confidence: 99%
“…In the mouse model, transplantation of total bone marrow cells has been known for almost 30 years to fully repopulate both the lymphoid and myeloid lineages of conditioned recipients (Abramson et al, 1977). A major advance in the field of HSC biology was the extensive characterization of the phenotype of murine HSCs.…”
Section: Phenotype and Function Of Tissue-specific Stem Cellsmentioning
confidence: 99%
“…Human hematopoietic stem cells (HSCs) have been identified in bone marrow (BM), peripheral blood and umbilical cord blood (CB) [1][2][3][4]. Initially, the functional capacity of the cells derived from these tissues was believed to be restricted to a hematopoietic cell fate.…”
Section: Introductionmentioning
confidence: 99%